2015
DOI: 10.1371/journal.pone.0118655
|View full text |Cite
|
Sign up to set email alerts
|

Potential Contribution of Phenotypically Modulated Smooth Muscle Cells and Related Inflammation in the Development of Experimental Obstructive Pulmonary Vasculopathy in Rats

Abstract: We tested the hypothesis that phenotypically modulated smooth muscle cells (SMCs) and related inflammation are associated with the progression of experimental occlusive pulmonary vascular disease (PVD). Occlusive PVD was induced by combined exposure to a vascular endothelial growth factor receptor tyrosine kinase inhibitor Sugen 5416 and hypobaric hypoxia for 3 weeks in rats, which were then returned to ambient air. Hemodynamic, morphometric, and immunohistochemical studies, as well as gene expression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…The rat model of PAH used in these studies exhibits hemodynamic and histological characteristics that worsen with time [ 19 ]. Additionally, inflammatory cells that accumulate around remodeled pulmonary vessels are dynamic in this animal model [ 20 ]. Prior studies have shown that at 8-weeks the hemodynamic profile of this model is severe PAH, the pulmonary vascular lesions range from concentric laminar smooth muscle to fully occluded and we confirmed ICAM-1 expression by staining control and late-stage PAH lung tissues (Additional file 1 : Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The rat model of PAH used in these studies exhibits hemodynamic and histological characteristics that worsen with time [ 19 ]. Additionally, inflammatory cells that accumulate around remodeled pulmonary vessels are dynamic in this animal model [ 20 ]. Prior studies have shown that at 8-weeks the hemodynamic profile of this model is severe PAH, the pulmonary vascular lesions range from concentric laminar smooth muscle to fully occluded and we confirmed ICAM-1 expression by staining control and late-stage PAH lung tissues (Additional file 1 : Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…VEGF also regulates growth and differentiation of type II pneumocytes, pointing to its critical role in the maintenance of "alveolar unit" normal functionality [43]. Blockade of such vital functions by SU could add to the alveolar damage induced by WPS exposure, enhancing the induction of a COPD picture, most notably by stimulating lung inflammatory cell infiltration, as reported by Otsuki et al [31].…”
Section: Discussionmentioning
confidence: 87%
“…Macrophages are a prominent component of the inflammatory infiltrates in experimental and clinical PAH 9,35,[71][72][73][74] and are thought to play a very important role in modulating the disease. 9,74 Macrophage depletion or inactivation is shown to prevent experimentally induced hypoxic PH and portopulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%